Benefits of regular walking exercise in advanced pre-dialysis chronic kidney disease - Kosmadakis, G. C. (2011)
There is increasing evidence of the benefit of regular physical exercise in a number of long-term conditions including chronic kidney disease (CKD). In CKD, this evidence has mostly come from studies in end stage patients receiving regular dialysis. There is little evidence in pre-dialysis patients with CKD Stages 4 and 5.